Peningkatan Keterampilan Praktik Siswa pada Pekerjaan Memasang Kosen melalui Teknik Make A Match - Sukardi, Sukardi (Universitas Muhammadiyah Magelang, 2019)
This Classroom Action Research aimed to improve students' skills in installing the board through the Make a Match. It was conducted at State Vocational School 1 of Magelang in Academic Year 2018/2019. The subjects were 30 students of Class XII of Bangunan C. It was conducted through 2 cycles, each of which was carried out through 2 meetings. The method of data collection was done through observation of observations of student skills and tests. The results of observations showed an increase in the number of students who reached score criteria, from 21 students (70%) in Cycle I to 28 students (93.33%) in Cycle II. Tests results also revealed an increase from 23 people (76%) to 30 people (100%). Thus, the Make a Match technique can improve students' skills in the practice of installing a board.